Experimental Study on Thermal Energy Storage Performance of Water Tank with Phase Change Materials in Solar Heating System. (2017) - Liang, Fei; Zhang, Yin; Liu, Qinjian; Jin, Zhenghao; Zhao, Xinhui; Long, Enshen
Abstract: The water tank（WS） with phase change material (PCM) for thermal energy storage (TES) has the characteristics of high heat storage density and great thermal storage capacity, and can effectively store solar energy resources. This paper tested the dynamin temperature change of a water tank immersed by phase change materials for thermal energy storage in solar heating system. The temperature change characteristics of the WS-PCM-TES in the charging process were obtained, and the thermal storage efficiency was analyzed. Combining with the engineering practice, this paper also put forward the way to optimize thermal storage performance of the phase change energy storage water tank.